Analisa Tekanan Mesin Screw Press Pabrik Minyak Kelapa Sawit di PT. Ujong Neubok Dalam - Teuku Muhammad Afriza Zaini; Sulaiman Ali; Maidi Saputra; Jamaluddin (LPPM Politeknik Aceh Selatan, 2022)
PT. Ujong Neubok Dalam (UND) is a company engaged in oil palm plantations and processing of Crude Palm Oil (CPO) and Kernel Palm Oil (PKO). In carrying out its production, the company has various variations of machines that are used to facilitate the production process, one of which is a screw press machine. A screw press is a machine used to chop and crush palm fruit to produce palm oil and separate oil from shells, nuts, and fibers. Screw press machines in CPO production have a very important role because if the screw press machine experiences insufficient pressure, it will affect the quality and quantity of the CPO oil produced. The purpose of this study was to analyze the magnitude of the effect of screw press pressure on the process of pressing fruit flesh into CPO at PT UND. The method used is a quantitative method through the calculation of screw press force, screw press pressure, and hydraulic pressure. The result obtained is that the pressure given by the screw press machine is 18.32 Bar / Psi with a standard hydraulic pressure that functions as a holder, namely 50-60 Bar / Psi, while the comparison analysis is known that the screw press pressure and hydraulic pressure at 50 Bar / Psi have a ratio of 1: 2, 7 and at 60 BarPsi have a ratio of 1: 3.2